Associations with Post-Consultation Health-Status in Primary Care Managed Acute Exacerbation of COPD - Gillespie,David; Francis,Nick; Ahmed,Haroon; Hood,Kerenza; Llor,Carl; White,Patrick; Thomas-Jones,Emma; Stanton,Helen; Sewell,Bernadette; Phillips,Rhiannon; Naik,Gurudutt; Melbye,Hasse; et al. (International Journal of Chronic Obstructive Pulmonary Disease, 2022)
David Gillespie,1,2 Nick Francis,3 Haroon Ahmed,4 Kerenza Hood,2 Carl Llor,5 Patrick White,6 Emma Thomas-Jones,2 Helen Stanton,2 Bernadette Sewell,7 Rhiannon Phillips,8 Gurudutt Naik,4 Hasse Melbye,9 Rachel Lowe,2 Nigel Kirby,2 Ann Cochrane,10 Janine Bates,2 Mohammed Fasihul Alam,11 Christopher Butler1 1Nuffield Department of Primary Care Health Sciences, University of Oxford, Oxford, England, UK; 2Centre for Trials Research, School of Medicine, College of Biomedical & Life Sciences, Cardiff University, Cardiff, Wales, UK; 3Primary Care, Population Sciences and Medical Education, University of Southampton, Southampton, England, UK; 4Division of Population Medicine, School of Medicine, Cardiff University, Cardiff, Wales, UK; 5University Institute in Primary Care Research Jordi Gol, Via Roma Health Centre, Barcelona, Spain; 6School of Population Health and Environmental Sciences, Kings College London, London, England, UK; 7Swansea Centre for Health Economics, Swansea University, Swansea, Wales, UK; 8Cardiff School of Sport & Health Science, Cardiff Metropolitan University, Cardiff, Wales, UK; 9General Practice Research Unit, Department of Community Medicine, UIT the Arctic University of Norway, Tromsø, Norway; 10York Trials Unit, Department of Health Sciences, University of York, York, England, UK; 11Department of Public Health, College of Health Sciences, QU-Health, Qatar University, Doha, QatarCorrespondence: David Gillespie, Nuffield Department of Primary Care Health Sciences, University of Oxford, Radcliffe Observatory Quarter, Woodstock Road, Oxford, England, OX2 6GG, UK, Email david.gillespie@phc.ox.ac.ukBackground: It has been demonstrated that antibiotic prescribing for Acute Exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD) can be safely reduced in primary care when general practitioners have access to C-reactive protein (CRP) rapid testing.Aim: To investigate the factors associated with post-consultation COPD health status in patients presenting with AECOPD in this setting.Design ...